Helicobacter pylori infection and relationship with endoscopic findings in patients treated at a referral endoscopic center in Panama - Duarte-Chang, Calixto (2021)
Introduction: Helycobacter pylori (HP) infection is a public health problem in Latin America with a prevalence of infection of up to 70%. There are endoscopic findings associated with the presence of infection, however we do not know the current prevalence in Panama and if the endoscopic findings are related to HP infection. Objective: To assess the frequency of HP infection in patients who underwent upper gastrointestinal endoscopy and its association with HP infection. Materials and methods: An observational, cross-sectional and analytical study was carried out from January 1, 2019 to December 31, 2019 in the Gastroenterology service of Hospital Santo Tomás, Panama city. The frequency of HP infection in patients who underwent upper gastrointestinal endoscopy and the association of endoscopic findings with HP infection was evaluated. Results: In total, 1,281 digestive endoscopies were performed. 21.4% of the patients included in the study confirmed HP infection. In endoscopic findings, the presence of nodular gastritis has an association OR 4.32 (2.74-6.80) with the presence of HP infection. The presence of duodenal ulcer and gastric ulcer were also significantly associated with the presence of HP infection, OR 3.71 (1.21-11.35) and OR: 2.59 (1.36-5.16). Conclusion: This is the first study in Panama to evaluate the association of endoscopic findings and the prevalence in a cohort of patients with an indication for upper endoscopy with the probability of Helicobacter pylori infection in the last decade. We conclude that certain endoscopic findings in an appropriate clinical context could increase the diagnostic probability of HP infection in patients seen in Panama.